Long-term stability of surgical-orthodontic open bite treatment: Le Fort I versus 4-piece segmental Le Fort I osteotomy - Silva, Vinicius Laranjeira Barbosa da (2018)
Introduction: This vertical malocclusion has the potential of causing functional and esthetic impairment, impacting patients´ quality of life negatively. The long-term stability of anterior open bite surgical-orthodontic treatment is an important and controversial issue. A variety of factors such as surgery type, surgery fixation, and the anteroposterior discrepancy is related to and can influence long-term overbite stability. The controversy of stability arises in the inherent difficulty of collecting a homogeneous sample, with considerable sample size and adequate long-term followup, leading the current literature to an inconclusive status. Therefore this thesis aimed to test 2 null hypotheses: 1- There is no difference in the long-term stability of the surgical-orthodontic correction of anterior open bite when comparing Le Fort I to 4-piece segmental Le Fort I osteotomies. 2- To test the null hypothesis that there is no difference in the long-term stability of the surgical-orthodontic correction of anterior open bite when comparing Class II to Class III patients. Materials and Methods: The sample of the first investigation comprised the lateral cephs of 29 open bite subjects treated with 1-piece Lefort I osteotomy compared to the lateral cephs of 24 open bite subjects treated with 4-piece Lefort I osteotomy; in both groups Class I, II and III subjects were included. The groups were matched regarding age and were compared with t-tests. To test the second null hypothesis, lateral cephs of 21 Class II open bite subjects were compared to lateral cephs of 25 Class III open bite subjects. Overbite changes were compared at 3-time points: T1 (pretreatment), T2 (posttreatment) and T3 (follow-up) by using t-test. Overbite clinical stability percentage at T3 was assessed with the chi-square test. Results: In 1-piece Le Fort I Group 65.52% of patients presented with clinically significant overbite stability, while in 4-piece Group 83.33% remained stable in the long-term, however it was not statistically significant. In Class II Group 57.14% of patients presented with clinically significant overbite stability, while in Class III Group 88% remained clinically stable, and it was statistically significant. Conclusions: The first null hypothesis regarding maxillary segmentation was accepted because there was no significant intergroup difference regarding the percentage of clinically stable patients. The type of fixation seems to influence the long-term stability of open bite surgical-orthodontic correction more than maxillary segmentation. The second null hypothesis was rejected because clinical stability of Class II malocclusion open bite surgical-orthodontic treatment was significantly smaller than in Class III malocclusions.